Influence of Sex on Current Methods of Adjusting Saddle Height in Indoor Cycling. Issue 2 (February 2021) - Encarnación-Martínez, Alberto; Ferrer-Roca, Ventura; García-López, Juan
Abstract : Abstract: Encarnación-Martínez, A, Ferrer-Roca, V, and García-López, J. Influence of sex on current methods of adjusting saddle height in indoor cycling. J Strength Cond Res 35(2): 519–526, 2021—The popularity of indoor cycling has increased in fitness centers, and therefore, proper bike fitting is important to avoid biomechanical-related injuries. However, no previous studies have compared the biomechanical kinematics of various existing protocols of saddle-height adjustment in indoor cycling. Furthermore, it was not clear if these protocols were appropriate for both men and women, as these equations were primarily obtained in male cyclists. Therefore, lower-limb joint kinematics were compared among 4 different protocols of saddle-height adjustment (1-Preferred, 2-Ferrer-Roca et al., 3-Lemond & Guimard, and 4-Static Goniometry) in 30 experienced indoor-cycling subjects (15 men and 15 women). Only 20–33% of the women had a knee extension while pedaling within the recommended range for each of the different protocols except for the preferred adjustment (73% were within). By contrast, all the protocols were moderately suitable for men (47–60% were within the recommended range). A multiple linear equation to estimate the recommended saddle height in both men and women ( R 2 = 0.917, p = 0.001) was obtained from the following variables: inseam length, stature, foot length, and knee angle. The differences in the findings between men and women may be partially explained by differences in anatomical structures, as well as the male-based equations, which argues the need for future investigations in female cyclists.